HUBUNGAN ANTARA KUALITAS LAYANAN DAN HARGA DENGAN KEPUASAN KONSUMEN COFFEE TOFFEE SURABAYA - Rahmadani, Rizky Arinda (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2016)
Many business cafe in Indonesia, especially in Surabaya makes the number of competition. Population on this research is the consumers that had visited one of Coffee Toffeeâs outlets in Surabaya. Samples are chosen with incidental sampling method. The result of this research: 1) shows the correlation between service quality and CoffeeToffee consumer satisfaction (r=0,664, p=0,000); 2) correlation between price and Coffee Toffee consumer satisfaction (r=0,486; p=0,000).